The effect of 8 weeks open and closed kinetic chain strength training on the torque of the external and internal shoulder rotator muscles in elite swimmers - Shahpar, F. M.; Rahnama, N.; Salehi, S. (Asian Journal of Sports Medicine, 2019)
Objectives:In accordance with the multiple causes of impingement syndrome being a major injury of the swimmers' shoulder, choosing an effective method in preventing shoulder injury is important. The purpose of this study was to compare the effect of eight weeks open and closed kinetic chain exercises on muscle torque of internal and external rotators of shoulder in elite swimmers.